3x-x-10=90

Simple and best practice solution for 3x-x-10=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-x-10=90 equation:


Simplifying
3x + -1x + -10 = 90

Reorder the terms:
-10 + 3x + -1x = 90

Combine like terms: 3x + -1x = 2x
-10 + 2x = 90

Solving
-10 + 2x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 2x = 90 + 10

Combine like terms: -10 + 10 = 0
0 + 2x = 90 + 10
2x = 90 + 10

Combine like terms: 90 + 10 = 100
2x = 100

Divide each side by '2'.
x = 50

Simplifying
x = 50

See similar equations:

| 2-15n=5(-3+z) | | -3x^2+24x-45=0 | | -3(-2x+1)-5=10 | | 15=6x-3x | | 3(x-4)+6=2x | | 3(q-5)=4a-(2a+4) | | 9(2K+3)+2=11(11K-11K) | | X-3x-10=90 | | x/6+14=0 | | 2x+7(2x-16)=48 | | 2x+7=-2x+5 | | 5r-18r-6=111 | | 6=-7/9+v | | 33333333n=33333333 | | [8(z+4)-19]-2(z-3)+2= | | 1/5a-27=7 | | 5x+6+1=17 | | -16=-1+4n+1 | | 6+14=0 | | 9(2K+3)+2=11(K-k) | | 4x-8+4x=-16 | | 3b-3=4b+9 | | -4x-4=36 | | 12x/12=35/12 | | 9=2r-3+6 | | 2x+1=x+111 | | 2x+7=2x+5 | | (3x+2y-1)dx=(2x-3y+1)dy | | -11/9x3/10 | | 8s-10=27-(3s-7) | | x+4+6x=-3 | | 3x+10x-(5x+9)= |

Equations solver categories